Formulation of an enzyme cocktail, HoloMix, using cellulolytic and xylanolytic enzyme core-sets for effective degradation of various pre-treated hardwoods - Malgas, Samkelo (Rhodes University, Faculty of Science, Department of Biochemistry and Microbiology, 2018)
Currently, there is a growing interest in utilising hardwoods as feedstocks for bioethanol production due to the vast advantages they have over other feedstocks for fermentable sugar production. In this study, two selected hardwoods, Acacia and Populus spp., were subjected to two pre-treatment processes (Sodium chlorite delignification and Steam explosion) and compared with respect to how these pre-treatments affect their enzymatic saccharification. Hardwoods were selected for this study, because hardwoods are easier to delignify when compared to softwoods, and therefore their polysaccharides are more easily accessible by enzymes for the purpose of producing fermentable sugars. Currently available commercial enzyme mixtures have been developed for optimal hydrolysis of acid-pre-treated corn stover and are therefore not optimal for saccharification of pre-treated hardwoods. In this work, we attempted the empirical design of a hardwood specific enzyme cocktail, HoloMix. Firstly, a cellulolytic core-set, CelMix (in a ratio of Egl 68%: Cel7A 17%: Cel6A 6%: Bgl1 9%), for the optimal release of glucose, and a xylanolytic core-set, XynMix (in a ratio of Xyn2A 60%: XT6 20%: AguA 11%: SXA 9%), for the optimal release of xylose, were formulated using an empirical enzyme ratio approach after biochemically characterising these enzymes. As it is well Ì¶ known that biomass pre-treatment may result in the generation of compounds that hamper enzymatic hydrolysis and microbial fermentation, the effects of these compounds on CelMix and XynMix were evaluated. Using the optimised CelMix and XynMix cocktails, a HoloMix cocktail was established for optimal reducing sugar, glucose and xylose release from the various pre-treated hardwoods. For delignified biomass, the optimized HoloMix consisted of CelMix to XynMix at 75% to 25% protein loading, while for the untreated and steam exploded biomass the HoloMix consisted of CelMix to XynMix at 93.75% to 6.25% protein loading. Sugar release by the HoloMix at a loading of 27.5 mg protein/g of biomass (or 55 mg protein/g of glucan) after 24 h gave 70-100% sugar yield. Treatment of the hardwoods with a laccase from Agaricus bisporus, especially wood biomass with a higher proportion of lignin, significantly improved saccharification by the formulated HoloMix enzyme cocktails. This study provided insights into the enzymatic hydrolysis of various pre-treated hardwood substrates and assessed whether the same lignocellulolytic cocktail can be used to efficiently hydrolyse different hardwood species. The present study also demonstrated that the hydrolysis efficiency of the optimised HoloMix was comparable to (if not better) than commercial enzyme preparations during hardwood biomass saccharification.
Keywords: Biomass; Cellulase; Hardwoods; Xylanases